Does marriage still matter? An evaluation of cohabitation in the light of Scripture - M. Davidson, Richard (2016)
As christians, we believe that marriage “is a divine institution of prime importance, which, according to Scripture, was given for all humankind by God Himself.” In addition, is “a commitment to exclusivity and permanence.” However, in many societies marriage is looked upon as optional, with some considering cohabitation to be a reasonable alternative. The present essay does not focus upon scientific research per se, but rather evaluates the practice of cohabitation and its effects in the light of Scripture.